Exposure to Virtual Social Stimuli Modulates Subjective Pain Reports - Jacob M Vigil; Daniel Torres; Alexander Wolff; Katy Hughes (Pain Research and Management)
BACKGROUND: Contextual factors, including the gender of researchers, influence experimental and patient pain reports. It is currently not known how social stimuli influence pain percepts, nor which types of sensory modalities of communication, such as auditory, visual or olfactory cues associated with person perception and gender processing, produce these effects.